Risk of Lyme disease: perceptions of residents of a Lone Star tick-infested community - Armstrong Philip M.; Brunet Laura Rosa; Spielman Andrew; Telford III Sam R. (The World Health Organization, 2001)
BACKGROUND: Lone Star ticks (Amblyomma americanum) have been suggested as a vector of the agent of Lyme disease (Borrelia burgdorferi sensu lato) in the USA, based on associations with an infection manifesting mainly as erythema migrans. In laboratory experiments, however, they failed to transmit B. burgdorferi sensu stricto. METHODS: In this study, carried out from 1994 to 1996, we determined the seroprevalences of B.burgdorferi (1.2%), Ehrlichia chaffeensis (7%), E. phagocytophila (0%), Rickettsia rickettsii (0%), R. typhi (0%), Coxiella burneti (0%), Francisella tularensis (0%), and Babesia microti (0%) by standard serological methods for 325 residents (97% of the total population) of Gibson Island, coastal Maryland, USA, where 15% of the residents reported having had Lyme disease within a recent 5-year span. FINDINGS: Of the 167 seronegative individuals who were followed up prospectively for 235 person-years of observation, only 2 (0.85%) seroconverted for B. burgdorferi. Of 1556 ticks submitted from residents, 95% were identified as Lone Star ticks; only 3% were deer ticks (Ixodes dammini), the main American vector of Lyme disease. B. burgdorferi s.s. infected 20% of host-seeking immature deer ticks, and borreliae ("B. lonestari") were detected in 1--2% of Lone Star ticks. Erythema migrans was noted in 65% of self-reports of Lyme disease, but many such reports indicated that the rash was present while the tick was still attached, suggesting a reaction to the bite itself rather than true Lyme disease. Sera from individuals reporting Lyme disease generally failed to react to B. burgdorferi or any other pathogen antigens. CONCLUSION: The residents of Gibson Island had an exaggerated perception of the risk of Lyme disease because they were intensely infested with an aggressively human-biting and irritating nonvector tick. In addition, a Lyme disease mimic of undescribed etiology (named Masters' disease) seems to be associated with Lone Star ticks, and may confound Lyme disease surveillance. The epidemiological and entomological approach used in this study might fruitfully be applied wherever newly emergent tickborne zoonoses have been discovered.